The effect of two levels of calcium carbide on reducing sugars, starch, and soluble pectin contents of Lacatan bananas - Reyes, Rosie Marilyn L.; Kabigting, Amelia L. (1968.)
Treatments using five and ten grams calcium carbide per 4.5 kilograms of Lacatan bananas hastened the degreening and the ripening processes of the fruits. This was evidenced by faster rate of production of reducing sugars and soluble pectin and hydrolysis of starch in the treated than in the untreated fruits. The treated bananas ripened three days earlier in the more mature fruits and sixteen days earlier in the less mature ones. At the ripe stage, the treated samples showed higher reducing sugar and pectin contents and lower starch than the untreated fruits; and in this respect, the five-gram treated samples were found even better than the ten-gram treated ones. The treated bananas were found significantly different from the untreated samples.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Bananas; Calcium carbide